Towards a single competition legislation for Malaysia / Lee Ching Yong - Lee, Ching Yong (2004)
The main objective of this study is to determine whether Malaysia should enact a single competition 1 legislation in the post-WTO era in the light of its existing laws. 2 The process of globalization and the influence of international bodies. such as. the United Nations Conference on Trade and Development (UNCT AD). the Asia-Pacific Economic Cooperation (APEC), and the advancement of information technology, have rendered competition law necessary for Malaysia. This study argues for the need of introducing a clear competition policy and comprehensive single competition legislation for Malaysia. The categories of anti-competitive practices will be identified and discussed in this dissertation. This dissertation will also propose a competition structure that is viable for Malaysia by considering relevant governmental policies and relevant existing laws.3 This study will evaluate the role played by the existing laws in dealing with the competition issues. Reference will be made to the competition law in the United Kingdom (UK), the European Union (EU), and other relevant competition regimes. This study is divided into three parts consisting of nine chapters. Chapter I provides the introduction of this study. Chapter 2 lays down the history and development of competition law in the UK and international bodies. Chapter 3 discusses the theory and objectives of competition law, and followed by chapter 4 which deals with the proposed structure of competition policy of Malaysia. As for chapter 5. it discusses the existing competition related laws in Malaysia. Chapter 6. 7 and 8 discuss the anti-competitive practices which consisting of horizontal restraints, vertical restraints, and mergers. This is fol lowed by Chapter 9 which provides the conclusion of this study.